The Effectiveness of Dialectical Behavior Therapy Skills Training Group vs. Cognitive Therapy Group on Reducing Depression and Suicide Attempts for Borderline Personality Disorder in Taiwan. Issue 1 (2nd January 2019) - Lin, Tsung-Jen; Ko, Huei-Chen; Wu, Jo Yung-Wei; Oei, Tian Po; Lane, Hsien-Yuan; Chen, Chung-Hey
Abstract : In this study the effectiveness of the condensed Dialectical Behavior Therapy Skills Training Group (DBTSTG) was compared to the Cognitive Therapy Group (CTG) in reducing depression and suicide reattempt and modifying emotion regulation strategies among those with borderline personality disorder (BPD). A total of 82 depressed BPD college students with a suicidal history within the past 6-months were randomly allocated to DBTSTG or CTG. Both groups had similar reductions in suicide reattempts and depression after the intervention and 6-month follow-ups. However, the CTG showed improvements in cognitive errors, but the DBTSTG revealed increases in acceptance and decreases in suppression scores. Both groups were effective in decreasing depression and suicide reattempt in BPD college students, probably through increasing adaptive antecedent-focused or response-focused strategies of emotion regulation, respectively.